2023
DOI: 10.2174/1568009623666230131124236
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene as a Potential Bioactive Compound: Chemistry, Extraction, and Anticancer Prospective

Abstract: Background: Lycopene, a potential bioactive agent, is a non-pro-vitamin A carotenoid recognized as a potent antioxidant. It is extracted from plants like tomatoes, watermelons, red carrots and papayas and has remarkable health benefits. A significant amount of research has been assisted to date to establish the anticancer activity of lycopene. Objective: Our review enhances information about the promising anticancer potential of this compound. Methods: The biological activity of lycopene has been described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Unlike β-carotene, lycopene lacks the β-angelone ring structure, preventing its conversion into vitamin A in the body[ 37 , 38 ]. Although it lacks the physiological activity of vitamin A, lycopene possesses a potent antioxidant function[ 38 , 39 ]. Cui, Lingling et al revealed that an appropriate dose of lycopene effectively reduces the incidence of ESC induced by JV-nitrosomethylbenzylamine (NMBzA) in F344 rats.…”
Section: Nps Regulate Oxidative Stress In Escmentioning
confidence: 99%
“…Unlike β-carotene, lycopene lacks the β-angelone ring structure, preventing its conversion into vitamin A in the body[ 37 , 38 ]. Although it lacks the physiological activity of vitamin A, lycopene possesses a potent antioxidant function[ 38 , 39 ]. Cui, Lingling et al revealed that an appropriate dose of lycopene effectively reduces the incidence of ESC induced by JV-nitrosomethylbenzylamine (NMBzA) in F344 rats.…”
Section: Nps Regulate Oxidative Stress In Escmentioning
confidence: 99%
“…Research has focused on its anti-cancer properties, including inhibiting apoptosis and cell proliferation and affecting various signal transduction pathways. Several studies highlighted its biological activity concerning skin cancers and photoprotection [205,206]. It has been shown that regular consumption of lycopene can protect the human skin from the effects of UVR, including erythema, alterations in the extracellular matrix, and damage to mitochondrial DNA [207].…”
Section: Lycopenementioning
confidence: 99%
“…During the early stage of UV-induced skin carcinogenesis, Nrf2 activation promotes the proliferation of normal cells, outnumbering precancerous cells and preventing their expansion and mutation. The antioxidant defense mediated by Nrf2, which is capable of handling excessive ROS formation in the human body, may be valuable in preventing ROS-mediated neoplastic transformation in the skin [205,206].…”
Section: Reactive Oxygen Species and Nmscmentioning
confidence: 99%